Development and characterization of microemulsions containing Tiliacora triandra Diels as an active ingredient for antioxidant and melanogenesis stimulating activities - Sitthiphong Soradech, Pokchut Kusolkumbot, Sirinan Thubthimthed (Journal of Applied Pharmaceutical Science, 2018)
The aimed of this study was to develop microemulsions comprising ethanolic leaf extract of the Tiliacora triandra Diels. (YL) as the potential active ingredient for antioxidant and melanogenesis stimulating activities. The YL extracts were prepared using macerating (MT) and batch stirring extraction (BSE) methods. The antioxidant and melanogenesis stimulating activities of each extracts with different extract conditions were investigated. The suitable condition was further developed to microemulsions (MEs). The pseudoternary phase diagram was developed for the MEs consisting oil mixture as an oil phase, tween 80 as a surfactant, 95% ethanol as a co-surfactant, and deionized water. The physicochemical properties, stability and cytotoxicity of the YL extract loaded ME were also evaluated. The results showed that YL extract from BSE method at 30°C exhibited high potential for DPPH radical scavenging and stimulating tyrosinase. No cytotoxic to human dermal skin fibroblast and melanoma (B16F10) cells at 0.001–1.0 mg/mL and its potential on stimulating melanin content at 0.05–1.0 mg/mL of YL extract were both achieved. Next, a study was designed to develop YL extract loaded microemulsions (ME). The optimized YL extract loaded ME had a droplet size in the range of 10.29 to 13.54 nm with narrow particle size distribution. All formulations of MEs showed good stability after accelerated condition. The release rate of the phenolic content of the YL extract from the ME was slower than that of the aqueous formulation. The YL extract loaded ME showed no cytotoxic to human dermal skin fibroblast and melanoma (B16F10) cells at 0.001 to 1.0 mg/mL. In conclusion, the obtained YL extract microemulsions exhibited good characteristics in terms of being a potential active ingredient in antioxidant and melanogenesis stimulating activities for anti-grey hair treatment.
Keywords: Microemulsions, Tiliacora triandra Diels, Antioxidant activity, Melanogenesis stimulating activity, Stability.